Soundwaves test book 3 [ developing listening and speaking skills - Messina; McNabney (New York: McGraw Hill, 2008)
CD 2 (unit 4 - Review unit 1 - 5)
CD 3 (unit 6 - unit 8)
CD 4 (unit 9 - Review units 6 - 10)
CD 5 (unit 11 - unit 13)
CD 7 (unit 16 - unit 18)
CD 8 (unit 19 - Review units 16 - 20)
CD 6 (unit 14 - Review units 11 - 15)
To accompany textbook titled "Soundwaves test book 3 : developing listening and speaking skills / Elida Beatriz Messina, Theodore McNabney"
Accompany with CD 1 to 8
ELC
Includes bibliographical references and index
Keywords: English language -- -- Composition and exercises